2020
DOI: 10.1101/2020.06.09.143040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of Rapid Sequences by Motor Cortex

Abstract: 1 Rapid execution of motor sequences is believed to depend upon the fusing of movement elements into 2 cohesive units that are executed holistically. We sought to determine the contribution of motor cortex 3 activity to this ability. Two monkeys performed highly practiced two-reach sequences, interleaved with 4 matched reaches performed alone or separated by a delay. We partitioned neural population activity 5 into components pertaining to preparation, initiation, and execution. The hypothesis that movement 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…At the other end of the spectrum, sequences of multiple movements are generated similarly by motor cortex regardless of overall sequence speed, which is presumably controlled by upstream / areas 38 . Thus, the broader point is not that there is any single strategy for speed-control across all types of behaviors, but rather that the network-dynamics perspective can often predict and/or explain the strategies employed by biological networks.…”
Section: Discussionmentioning
confidence: 99%
“…At the other end of the spectrum, sequences of multiple movements are generated similarly by motor cortex regardless of overall sequence speed, which is presumably controlled by upstream / areas 38 . Thus, the broader point is not that there is any single strategy for speed-control across all types of behaviors, but rather that the network-dynamics perspective can often predict and/or explain the strategies employed by biological networks.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is also consistent with results from neurophysiology (31) and magneto-encephalography (MEG; 32), showing the first action in a sequence is most highly activated in premotor and motor areas during the preparatory period. Since M1 does not contain representation of sequence identity, continuous signals from higher-order regions provide it with the sequential context needed throughout the sequence production (8,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not show differential activation for different trained sequences, thus no sequence representation as defined here. Moreover, recent electrophysiological studies have also shown that M1 does not represent the sequential context (Russo et al, 2020; Zimnik and Churchland, 2021). Altogether, this makes it unlikely that the RS observed in M1 reflects sequence dependency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a more likely scenario is that planning and execution occur in overlapping neuronal populations, but occupy orthogonal subspaces of the multidimensional neuronal code (Fig. 8B), such that planning activity does not trigger motor output (Kaufman et al, 2014; Lara et al, 2018; Zimnik and Churchland, 2020). Finally, an intriguing possibility that should be investigated in future studies is that multiple future movements could be planned as an integrated packet (i.e., as a movement chunk), such that there is only one, shared, planning subspace, with specialized code for specific transitions (i.e., 2-3) in movement sequences.…”
Section: Discussionmentioning
confidence: 99%